Investigation of the effect of Calendula officinalis extract on preventing radiotherapy-induced oral mucositis - Moslemi, Dariush; Babaee, Neda; Khalilpour, Mohammad; Vejdani, Fatemeh; Bijani, Ali; Moghadamnia, Ali akbar; Ameri, Ahmad (Reports of Radiotherapy and Oncology, 2025)
Objective: The objective of this study was to investigate the effect of Calendula officinalis mouthwash on preventing radiotherapy-induced Oral Mucositis Materials and Methods: Patients with head and neck cancers referred to our center for radiotherapy were divided into two groups, one receiving drug and the other group receiving placebo. Patients in the drug group received 2% Calendula gel. Oral Mucositis Assessment Scale was used to evaluate oral mucositis intensity at the end of each week. The scale of mucositis at the end of each week was compared between groups. Results: Calendula gel significantly decreased the intensity of oral mucositis as compared to placebo at the end of the 2nd (p=0.019), 3rd (p<0.0001) and 6th week (p=0.031). Conclusion: Calendula gel could be effectively used to decrease the intensity of radiotherapy- induced oral mucositis.